ENVIRONMENTAL IMPROVEMENT OF A BUILDING’S UNDERGROUND FLOORS IN HEBRON, PALESTINE - Alatawneh, Bader; Abureesh, Noor; Qadi, Jenan (1st International Architectural Sciences and Application, 2021)
Improving the underground spaces in an environmental approach facilitates the use of theses spaces besides the energy saving. However, the issue concerned with lighting and natural ventilation has become a major challenge in order to use the underground spaces in its current process. Underground floors require good ventilation to acquire comfortable environment, in addition to the lighting systems that play a significant role in this experience, where people always need to navigate such spaces easily and safely. Nowadays, the artificial illumination and mechanical ventilation are commonly used to get good lighting and air quality in underground spaces, while these systems consume more energy. This research aims to enhance the natural lighting and ventilation in underground spaces in order to enhance the quality of these space. To achieve this goal, a research methodology has been developed to study the problems of ventilation and lighting that face the underground floors of the parking central building of Hebron city in Palestine, which was randomly selected. The study focuses testing the appropriate solutions to solve the problems of daylight and ventilation in an efficient way. Dependently, the main result of the research is a highlight of the alternative passive design solutions those can be adopted in any retrofit process in order to enhance the natural lighting, ventilation and reduce energy use in these spaces.
Keywords: Underground Floor, Daylight, Ventilation, Passive Solutions.